Deep Brain Stimulation Impedance Decreases Over Time Even When Stimulation Settings Are Held Constant - Satzer, David; Yu, Huiyan; Wells, Meredith; Padmanaban, Mahesh; Burns, Matthew R.; Warnke, Peter C.; Xie, Tao (Frontiers in Human Neuroscience, 2020)
Objectives: To study whether and to what extent the therapeutic impedance and current change under long-term deep brain stimulation (DBS) with constant stimulation settings, which could inform the role of constant current stimulation. Methods: Therapy impedance and current measurements were retrospectively collected from patients with Parkinson’s disease (PD) undergoing DBS of subthalamic nucleus (STN) or essential tremor (ET) undergoing ventral intermediate nucleus (VIM). Baseline and follow-up measurements were obtained for intervals of at least 6 months without changes in stimulation settings. The single longest interval of constant stimulation for each electrode was included. Temporal trends in impedance and current were analyzed as absolute and relative differences and as rate of change. Results: Impedance and current data from 79 electrodes (60 in STN, 19 in VIM) in 44 patients (32 with PD, 12 with ET) met inclusion criteria. Duration between baseline and follow-up measurements with constant stimulation settings was 17 months (median, with interquartile range of 12-26 months) in the mixed group. Therapy impedance decreased by 27 ± 12 Ω/year (mean ± 2 standard errors; p < 0.0001), and therapy current increased at a rate of 0.142 ± 0.063 mA/year (p < 0.0001). Similar results were observed in the STN and VIM subgroups. Conclusions: Impedance decreases gradually over time, even when stimulation settings are kept constant. The rate of decrease is smaller than previously reported, suggesting that changes in stimulation settings contribute to impedance drift. Stimulation-independent impedance drift is gradual but relevant to constant-current programming.